Optical genome mapping, a promising alternative to gold standard cytogenetic approaches in a series of acute lymphoblastic leukemias - Lestringant, Valentin; Duployez, Nicolas; Penther, Dominique; Luquet, Isabelle; Derrieux, Coralie; Lutun, Anne; Preudhomme, Claude; West, Michaela; Ouled‐Haddou, Hakim; Devoldere, Catherine; Marolleau, Jean‐Pierre; Garçon, Loïc; et al. (Genes chromosomes & cancer, 2021)
Acute lymphoblastic leukemias (ALL) are characterized by a large number of cytogenetic abnormalities of clinical interest that require the use of several complementary techniques. Optical genome mapping (OGM) is based on analysis of ultra‐high molecular weight DNA molecules that provides a high‐resolution genome‐wide analysis highlighting copy number and structural anomalies, including balanced translocations. We compared OGM to standard techniques (karyotyping, fluorescent in situ hybridization, single nucleotide polymorphism‐array and reverse transcription multiplex ligation‐dependent probe amplification) in 10 selected B or T‐ALL. Eighty abnormalities were found using standard techniques of which 72 (90%) were correctly detected using OGM. Eight discrepancies were identified, while 12 additional anomalies were found by OGM. Among the discrepancies, four were detected in raw data but not retained because of filtering issues. However, four were truly missed, either because of a low variant allele frequency or because of a low coverage of some regions. Of the additional anomalies revealed by OGM, seven were confirmed by another technique, some of which are recurrent in ALL such as LMO2‐TRA and MYC‐TRB fusions. Despite false positive anomalies due to background noise and a case of inter‐sample contamination secondarily identified, the OGM technology was relatively simple to use with little practice. Thus, OGM represents a promising alternative to cytogenetic techniques currently performed for ALL characterization. It enables a time and cost effective analysis allowing identification of complex cytogenetic events, including those currently inaccessible to standard techniques.